The Discovery and Characterization of Targeted Perikaryal-Specific Brain Lesions With Excitotoxins - Coyle, Joseph T.; Schwarcz, Robert (Frontiers in Neuroscience, 2020)
The neurotoxic action of glutamic acid was first described by Lucas and Newhouse, who demonstrated neural degeneration in the inner layers of the neonatal mouse retina after systemic treatment with L-glutamate. Olney extended these findings by showing that neuronal degeneration affected other brain structures including neurons within the arcuate nucleus of the hypothalamus and the area postrema, that the lesion spared axons passing through these areas, and that neurotoxic potency of glutamate analogues correlated with their excitatory potency resulting in the designation: “excitotoxins”. As this method affected only a small number of brain regions, it was not suitable for targeted brain lesions. The Coyle laboratory showed that direct injection of the potent glutamate receptor agonist, kainic acid, into the rat striatum caused a rapid degeneration of intrinsic neurons while sparing axons of passage or termination including the unmyelinated dopaminergic terminals. Kainic acid exhibited this perikaryal specific and axon sparing profile when injected into the cerebellum, hippocampus and eye. However, neuronal vulnerability was highly variable with hippocampal CA3, pyriform cortex and amygdala neurons exhibiting great sensitivity. In a comparison study, Ibotenic acid, a potent NMDA receptor agonist isolated from the amanita muscaria mushroom, was found to have neurotoxicity potency comparable to kainate but without the seizures. Schwarcz’s studies demonstrated that ibotenate produced spherical, perikaryal specific lesions regardless of the site of injection. Antagonist studies confirmed that its effects were mediated by the N-methyl-D-aspartate receptor. Because of this uniform neurotoxicity, near ubiquitous efficacy and lack of seizures, ibotenic acid has now become the excitotoxic lesion agent of choice.